Relationship between Succinate Transport and Production of Extracellular Poly(3-Hydroxybutyrate) Depolymerase in Pseudomonas lemoignei - Terpe, Kay (American Society for Microbiology, 1999)
The relationship between extracellular poly(3-hydroxybutyrate) (PHB) depolymerase synthesis and the unusual properties of a succinate uptake system was investigated in Pseudomonas lemoignei. Growth on and uptake of succinate were highly pH dependent, with optima at pH 5.6. Above pH 7, growth on and uptake of succinate were strongly reduced with concomitant derepression of PHB depolymerase synthesis. The specific succinate uptake rates were saturable by high concentrations of succinate, and maximal transport rates of 110 nmol/mg of cell protein per min were determined between pH 5.6 and 6.8. The apparent K(S0.5) values increased with increasing pH from 0.2 mM succinate at pH 5.6 to more than 10 mM succinate at pH 7.6. The uptake of [(14)C]succinate was strongly inhibited by several monocarboxylates. Dicarboxylates also inhibited the uptake of succinate but only at pH values near the dissociation constant of the second carboxylate function (pK(a)2). We conclude that the succinate carrier is specific for the monocarboxylate forms of various carboxylic acids and is not able to utilize the dicarboxylic forms. The inability to take up succinate(2−) accounts for the carbon starvation of P. lemoignei observed during growth on succinate at pH values above 7. As a consequence the bacteria produce high levels of extracellular PHB depolymerase activity in an effort to escape carbon starvation by utilization of PHB hydrolysis products.